2019
DOI: 10.1111/1754-9485.12979
|View full text |Cite
|
Sign up to set email alerts
|

Urologists’ referral and radiation oncologists’ treatment patterns regarding high‐risk prostate cancer patients receiving radiotherapy within 6 months after radical prostatectomy: A prospective cohort analysis

Abstract: Introduction Previous studies have observed low rates of adjuvant radiotherapy after radical prostatectomy (RP) for high‐risk prostate cancer patients. However, it is not clear the extent to which these low rates are driven by urologists’ referral and radiation oncologists’ treatment patterns. Method The Clinician‐Led Improvement in Cancer Care (CLICC) implementation trial was conducted in nine public hospitals in New South Wales, Australia. Men who underwent RP for prostate cancer during 2013–2015 and had at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Lack of familiarity with other treatment modalities [85] and concerns about treatment side effects can also limit referrals for radiation oncology [86,87]. Treatment patterns have been found to vary widely for prostate cancer patients in Australia, for example, depending on whether patients were referred to a radiation oncologist (RO) as well as a surgeon [88] with fewer than 14% consulting with an RO prior to surgery [89]. Addressing these referral issues requires a systems-level focus, to define and promote optimal referral pathways, rather than relying on individual GPs to appropriately refer patients to multidisciplinary care, as they typically see relatively few new cancer diagnoses each year.…”
Section: Plos Onementioning
confidence: 99%
“…Lack of familiarity with other treatment modalities [85] and concerns about treatment side effects can also limit referrals for radiation oncology [86,87]. Treatment patterns have been found to vary widely for prostate cancer patients in Australia, for example, depending on whether patients were referred to a radiation oncologist (RO) as well as a surgeon [88] with fewer than 14% consulting with an RO prior to surgery [89]. Addressing these referral issues requires a systems-level focus, to define and promote optimal referral pathways, rather than relying on individual GPs to appropriately refer patients to multidisciplinary care, as they typically see relatively few new cancer diagnoses each year.…”
Section: Plos Onementioning
confidence: 99%
“…The differences between specialty groups regarding the use and timing of post-prostatectomy RT is consistent with previous Australian and North American surveys which demonstrated low rates of referral to ROs for high-risk patients in the 6 months following RP, and greater hesitancy amongst urologists than ROs to recommend adjuvant RT in a variety of hypothetical scenarios. [9][10][11][12] Of note, these patterns of practice surveys were conducted prior to the recent publication of several large, randomised trials supporting the oncological efficacy of early salvage RT over immediate adjuvant RT. The reasons for these low rates of referrals may include selection and referral biases, patient-related factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This should not be difficult given the availability of electronic data systems that contain this information. Relying on occasional retrospective analyses of relatively old data, such as the paper in this edition of the journal, does not sufficiently close the quality loop efficiently and similar past papers 2,9,13,17–23 suggest that while highlighting the problem, they do not necessarily lead to the changes that are required. This must change – proactive, regular national reporting, along with a suite of other pro‐active initiatives promoting evidence‐based radiotherapy, needs to occur.…”
mentioning
confidence: 98%
“…Therefore, a significant minority of this study sub-population have missed out on therapy that could lift their survival substantially. It has also been highlighted that adjuvant radiotherapy referral rates are low for high-risk prostate cancer patients 17 and lymphoma patients 12 just as two other examples where evidence is not being followed. Batumalai et al have identified the significant overall survival detriment omitting radiotherapy can have on a population with low radiotherapy rates.…”
mentioning
confidence: 99%